1995
DOI: 10.1063/1.113625
|View full text |Cite
|
Sign up to set email alerts
|

Thermal conduction normal to diamond-silicon boundaries

Abstract: Passive diamond layers fabricated using chemical vapor deposition can improve thermal conduction in electronic microstructures. The benefit of using diamond depends strongly on the thermal boundary resistance between active semiconducting regions, where heat is generated, and the diamond. Two independent experimental methods measure the total thermal resistance for conduction normal to 0.2, 0.5, and 2.6 μm thick diamond layers deposited on silicon, providing an upper bound for the effective silicon-diamond bou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
13
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 13 publications
4
13
0
Order By: Relevance
“…Some of these8-19.21.22 were included by Goodson et al in fig. 4 of ref 19. We have replotted these data in Fig.…”
Section: Fine-grained Filmsmentioning
confidence: 91%
“…Some of these8-19.21.22 were included by Goodson et al in fig. 4 of ref 19. We have replotted these data in Fig.…”
Section: Fine-grained Filmsmentioning
confidence: 91%
“…For instance, the results of Graebner et al [8] indicate a strong dependence on the layer thickness for both components of k, with an anisotropy k vertical /k lateral ≈ 2 (for thicknesses in the range of 30-100 µm) and values eventually reaching the natural diamond ones in both directions for film thicknesses above 200 µm. Evidence of strong thickness dependence of the thermal conductivity was observed also in thinner, columnar-structured NCD films by Philip et al [7], who reported an increase in the thermal conductivity from 530 to 1370 Wm -1 K -1 , when the film thickness increased from 1.6 µm to 3.6 µm.…”
Section: Introductionmentioning
confidence: 99%
“…Scattering at the grain boundaries is the main phonon scattering mechanism [8,9] in such polycrystalline material. The anisotropy in the shape of the grains, with an out-of-plane (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The high-temperature gradient results in high thermal stresses, which may cause de-bonding of the interface, thus reducing the function and reliability of the systems. A better understanding of temperature and thermal flux distributions in the bonded media is critical in many applications.In the literature, numerous studies have been reported on the investigation of thermal conduction in particle composites and multi-layered media [1][2][3][4][5][6][7][8][9][10]. To the authors' best knowledge, the thermal behavior of bi-layer materials with an interface inclusion has not been investigated for finite media.…”
mentioning
confidence: 96%